Baseline apnea-hypopnea index threshold and adenotonsillectomy consideration in children with OSA. (December 2021) - Gourishetti, Saikrishna C.; Hamburger, Emily; Pereira, Kevin D.; Mitchell, Ron B.; Isaiah, Amal
Abstract: Objectives: Adenotonsillectomy (AT) is the first line of treatment for pediatric obstructive sleep apnea (OSA). In some treatment guidelines, children with moderate to severe OSA, defined as apnea-hypopnea index (AHI) ≥ 5, may be recommended AT regardless of symptoms. The differences in outcomes between children randomized to watchful waiting with supportive care (WWSC) or AT were compared based on baseline OSA severity threshold of AHI≥ 5. Methods: A secondary analysis of the Childhood Adenotonsillectomy Trial, a randomized controlled trial of children with OSA aged 5–9 years who underwent AT or WWSC, was performed. The primary outcome was the change in neurocognition measured by Developmental Neuropsychological Assessment (NEPSY). Secondary outcomes included changes in behavior, symptoms of OSA, and quality of life. Outcomes were measured at baseline and the seven-month follow-up after grouping children based on whether their AHI was greater than or equal to 5. Comparisons were performed using two-way analysis of covariance (ANCOVA) while controlling for age, sex and race. Differences in treatment effect were measured using Cohen's d . Results: Of the 397 children included, 203 received WWSC and 194 underwent AT. The treatment effects on post-randomization changes in neurocognition, measured by NEPSY in children with AHI ≥5 (Cohen's d = 0.1 [95% CI, −0.1 to 0.4]) was not significantly different from children with AHI <5 (Cohen's d = 0.1 [95% CI, −0.1 to 0.4]). Furthermore, among children in the AT group alone, the effects of AT on post-treatment changes in NEPSY did not differ based on AHI threshold (Cohen's d = −0.06 [95% CI, −0.3 to 0.2]). Additionally, the treatment effects on post-randomization changes in behavior, symptoms, and quality of life did not vary based on AHI threshold. Conclusion: The outcomes of neurocognition, behavior, symptoms, and quality of life did not differ between children with OSA randomized to WWSC or AT based on OSA severity threshold alone. Additionally, the effects of AT on post-treatment outcomes did not differ based on AHI threshold. Highlights: Treatment effects following watchful waiting and eAT do not vary based on OSA severity alone. Post-adenotonsillectomy changes in outcomes do not vary based on AHI threshold. No differences in neurocognition, behavior, symptoms and QOL based on AHI severity.